2020
DOI: 10.1111/jam.14664
|View full text |Cite
|
Sign up to set email alerts
|

Aporphinoid alkaloids inhibit biofilm formation of Yersinia enterocolitica isolated from sausages

Abstract: Aims of the study The ability of Yersinia enterocolitica strains to form biofilms and the capacity of different alkaloids to inhibit biofilm formation were investigated. Methods and Results The capacity to form biofilm on polystyrene of 31 Y. enterocolitica strains was evaluated. Biofilm and quorum sensing (QS) inhibition of 17 alkaloids were assayed; furthermore, minimum biofilm inhibitory concentration (MBIC) was determined. The capacity to form biofilms among the examined strains seemed to be a strain‐relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…It was reported that Y. enterocolitica could form biofilms, which might be related to its pathogenicity, antibiotic resistance, and virulence ( Ioannidis et al, 2014 ; Di Marco et al, 2020 ). Therefore, it was necessary to evaluate the effect of CA on the biofilm of Y. enterocolitica .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that Y. enterocolitica could form biofilms, which might be related to its pathogenicity, antibiotic resistance, and virulence ( Ioannidis et al, 2014 ; Di Marco et al, 2020 ). Therefore, it was necessary to evaluate the effect of CA on the biofilm of Y. enterocolitica .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this study, the down-regulation of kdpD might lead to the growth inhibition of Y. enterocolitica by this way. Furthermore, the KdpD/KdpE system has also been proven to exert influence on the expression of flagella-related genes and the flagella formation of avian pathogenic E. coli ( Xue et al, 2020 ), which is essential for the motility and toxicity of bacteria ( Yang et al, 2014 ), and has a critical role at the beginning of the biofilm formation of B. cereus and Y. enterocolitica ( Di Marco et al, 2020 ). So, the down-regulation of kdpD might affect the biofilm formation of Y. enterocolitica.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such inhibitors are homoserine lactone-like TGK series, cladodionen, 3-amino2-oxazolidinone YXL-13, ε-polysine, gingerol, aporphinoid alkaloids, etc. [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 ]. A QS inhibitor, 4- hydroxy-3-methoxy benzaldehyde (Vanillin), when applied to reverse osmosis (RO) membrane, decreases biofilm formation by up to 45%.…”
Section: Qs-mediated Biofilm Regulation Methods In Wastewater Treatme...mentioning
confidence: 99%
“… poultry, slaughterhouse stainless steel, surface-water isolates, human epithelial cells [ [68] , [69] , [70] ] 2 Salmonella spp. pig farm, poultry eggshells, glass, broiler bedding material, polystyrene [ 15 , [71] , [72] , [73] , [74] ] 3 Escherichia coli broiler material broiler bedding material, air-handling system, water [ 75 ] 4 Yersinia enterocolitica mammals flea intestine (vector of disease), polystyrene [ 76 , 77 ] 5 Listeria monocytogenes pork processing industry, floor drain and drain water, poultry meat stainless steel, glass [ [78] , [79] , [80] , [81] , [82] ] Staphylococcus aureus bovines bovine magpie [ 83 ] Enterococcus faecalis cattle farm intestine [ 84 ] Mycoplasma hyopneumoniae pig farm tracheal epithelium from pigs, glass [ 85 ...…”
Section: Biosafety Tools For the Livestock Sectormentioning
confidence: 99%